2010
DOI: 10.4103/0255-0857.66489
|View full text |Cite
|
Sign up to set email alerts
|

Early onset primary pulmonary cryptococcosis in a renal transplant patient

Abstract: We report a case of primary pulmonary cryptococcosis in a post-renal transplant patient. A 65-year-old male renal transplant patient was admitted to the hospital with a low grade fever of 1 month, radiologically mimicking tuberculosis (TB). Broncho-alveolar fluid (BAL) shows capsulated yeast, and Cryptococcus neoformans was grown on culture supported by cytology and histopathological examination. Cryptococcal antigen was positive (32-fold) in serum and was negative in cerebrospinal fluid (CSF). The patient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Of note, in one study, the mortality rate of cryptococcosis in countries where ART is available was found to be 15-20%, compared to a mortality rate of 32% in countries without readily accessible ART, such as Uganda [16][17]. It is important to note that the use of ART in HIV patients is essential for avoiding relapse of cryptococcal meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in one study, the mortality rate of cryptococcosis in countries where ART is available was found to be 15-20%, compared to a mortality rate of 32% in countries without readily accessible ART, such as Uganda [16][17]. It is important to note that the use of ART in HIV patients is essential for avoiding relapse of cryptococcal meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Deeper fragments which included crusty deposits from the junction of nail were collected with the help of sterile scissors or nail clippers. These were used for microscopy as well as culture [11][12][13][14][15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…All culture slants were examined routinely for presence of fungal growth with respect to the colonial appearance like size, surface, color, margin, texture, diffusion of pigmenting the media. Findings were recorded weekly for a period of 3 weeks & negative cultures were discarded after 3 weeks [11][12][13][14][15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations